Scared Straight? Threat and Assimilation of Refugees in Germany - Philipp Jaschke; Sulin Sardoschau; Marco Tabellini (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper studies the effects of local threat on cultural and economic assimilation of refugees, exploiting plausibly exogenous variation in their allocation across German regions between 2013 and 2016. We combine novel survey data on cultural preferences and economic outcomes of refugees with corresponding information on German respondents, and construct a threat index that integrates contemporaneous and historical variables. On average, refugees assimilate both culturally and economically. However, while refugees assigned to more hostile regions converge to German culture more quickly, they do not exhibit faster economic assimilation. Our evidence suggests that refugees exert more assimilation effort in response to local threat, but that higher discrimination prevents them from integrating more quickly in more hostile regions.
Keywords: F22; J15; Z10; 330; refugees; cultural change; assimilation; identity